Nuclear-encoded factors associated with the chloroplast transcription machinery of higher plants - Yu, Qing-Bo; Huang, Chao; Yang, Zhong-Nan (Frontiers in Plant Science, 2014)
Plastid transcription is crucial for plant growth and development. There exist two types of RNA polymerases in plastids: a nuclear-encoded RNA polymerase (NEP) and plastid-encoded RNA polymerase (PEP). PEP is the major RNA polymerase activity in chloroplast. Its core subunits are encoded by the plastid genome, and these are embedded into a larger complex of nuclear-encoded subunits. Biochemical and genetics analysis identified at least twelve proteins are tightly associated with the core subunit, while about thirty-four further proteins are associated more loosely generating larger complexes such as the transcriptionally active chromosome or a part of the nucleoid. Domain analyses and functional investigations suggested that these nuclear-encoded factors may form several functional modules that mediate regulation of plastid gene expression by light, redox, phosphorylation, and heat stress. Genetic analyses also identified that some nuclear-encoded proteins in the chloroplast that are important for plastid gene expression, although a physical association with the transcriptional machinery is not observed. This covers several PPR proteins including CLB19, PDM1/SEL1, OTP70 and YS1 which are involved in the processing of transcripts for PEP core subunit as well as AtECB2, Prin2, SVR4-Like and NARA5 that are also important for plastid gene expression, although their functions are unclear.